Los manuales de convivencia en las escuelas católicas colombianas - Beltrán Sánchez, Santiago (2022)
The aspiration of state, ministerial and teacher institutions to achieve a school free of conflicts, quarrels and disruptions in Colombia is a challenge of yesteryear. In this way, behavioral regulation materializes historically through different texts (Carreño’s manual, catechisms, school regulations, to name a few), to the point of configuring the current manuals of coexistence, which seek in a procedural and instructional way to mitigate at all costs the violent demonstrations of the school. To enter into this problem, some characteristics of the coexistence manuals of Catholic schools will be presented, relating them to the debates on Colombian school coexistence. In this way, the present text seeks to distinguish the concept of civilization from that of culture, explaining the genesis of behavior and the current analysis perspectives, those that have the intention of solving the problem of coexistence from the discussion for what legislative or legal.